Cloud-based tools for teaching higher mathematics to future engineers: the USA experience - N. M. Kiianovska (Academy of Cognitive and Natural Sciences, 2013)
Among the components of fundamental training of an engineer as a highly qualified specialist is the acquisition of knowledge in higher mathematics and the ability to apply the acquired knowledge in professional activities. One of the countries where the use of information and communication technologies in teaching higher mathematics to engineering students is given due attention is the United States of America. The basic level of engineering education in the USA is a bachelor's degree (4 years). There is no government industry standard for higher education in the United States: there is a strong accreditation system led by ABET (Accreditation Board for Engineering and Technology), a non-governmental organization, which, in particular, evaluates the quality of training in engineering specialties based on the "Engineering Criteria 2000" (Engineering Criteria 2000 - EC2000). The third criterion defines the requirements to the knowledge and skills of engineering graduates, among which the "ability to apply applied knowledge in mathematics, science and engineering in professional activities" has a high weight.